"Burn me too." One family's history of remembering and forgetting - Gelbart, Petra (Romano džaniben, 2024)
The text was presented by Petra Gelbart on 19 April 2023 at the international conference `Roma, Jews and the Holocaust' at Yale University. The conference focused on the experiences of Romani and Jewish holocaust survivors and their entaglements during and after the Second World War. The event. Also featured the presentation of Ari Joskowicz's new book Rain of Ash: Roma, Jews and the Holocaust (Princeton University Press 2023). The text by Petra Gelbart was written partly as a commentary on the book and partly as a testimony to some of the Romani efforts to gain equal recognition for the Holocaust of the Roma and Sinti in the U.S. and international institutions.
Keywords: Roma; holocaust; the struggle for recognition of the Holocaust of Roma and Sinti